Genetic variation and gastric cancer risk: a field synopsis and meta-analysis. Issue 8 (2nd March 2015) - Mocellin, Simone; Verdi, Daunia; Pooley, Karen A; Nitti, Donato
Abstract : Background: Data on genetic susceptibility to sporadic gastric carcinoma have been published at a growing pace, but to date no comprehensive overview and quantitative summary has been available. Methods: We conducted a systematic review and meta-analysis of the evidence on the association between DNA variation and risk of developing stomach cancer. To assess result credibility, summary evidence was graded according to the Venice criteria and false positive report probability (FPRP) was calculated to further validate result noteworthiness. Meta-analysis was also conducted for subgroups, which were defined by ethnicity (Asian vs Caucasian), tumour histology (intestinal vs diffuse), tumour site (cardia vs non-cardia) and Helicobacter pylori infection status (positive vs negative). Results: Literature search identified 824 eligible studies comprising 2 530 706 subjects (cases: 261 386 (10.3%)) and investigating 2841 polymorphisms involving 952 distinct genes. Overall, we performed 456 primary and subgroup meta-analyses on 156 variants involving 101 genes. We identified 11 variants significantly associated with disease risk and assessed to have a high level of summary evidence: MUC1 rs2070803 at 1q22 (diffuse carcinoma subgroup), MTX1 rs2075570 at 1q22 (diffuse), PSCA rs2294008 at 8q24.2 (non-cardia), PRKAA1 rs13361707 5p13 (non-cardia), PLCE1 rs2274223 10q23 (cardia), TGFBR2 rs3087465 3p22 (Asian), PKLR rs3762272 1q22 (diffuse), PSCA rs2976392 (intestinal), GSTP1 rs1695 11q13 (Asian), CASP8 rs3834129 2q33 (mixed) and TNF rs1799724 6p21.3 (mixed), with the first nine variants characterised by a low FPRP. We also identified polymorphisms with lower quality significant associations (n=110). Conclusions: We have identified several high-quality biomarkers of gastric cancer susceptibility. These data will form the backbone of an annually updated online resource that will be integral to the study of gastric carcinoma genetics and may inform future screening programmes.